Respon Jepang terhadap Kebangkitan Militer Tiongkok. - Retno Indah Nurita (HI 14 UMY183, 2014)
The Tiongkok‟s rapid economic growth coupled with the weapon modernization has caused more concern in most countries, mainly in the Asia Pacific region. Even though the Chinese government has explained the reason for the development of their military and actively supports economic activities in other Pacific countries, it does not reduce the threats felt by certain countries in the region, particularly Japan. As a result, Japan had come to make a change in a military strategy, supported by the United States power. This situation further aggravated the peace and security in the Asia Pacific region. Not only Tiongkok and Japan relations will be even hotter, this situation also raises concern of the countries in the region. The presence of the United States, unresolved political issues with Taiwan, the increasing tension of the seizure of the water in the East Tiongkok Sea and South Tiongkok Sea, coupled with the suspicion related to the history of the past, making the action-reaction between Tiongkok and Japan disturb stability in the region. This paper will analyze the response Japan about Tiongkok military with regards to their military strategy and wether their strategy will promote cooperation or on the contrary provoke competition in Asia Pacific. This paper will particularly answer some questions such as how does Japan perceive Tiongkok military strategy, what factors have triggered Japanese government to change its defense policy. Keywords : threat perception, security dilemma, military strategy